1889 N.Y. Laws 167, § 2 - (:unkn) unknown (My University, 1889)
Ch. 140 § 2: Prohibited using, intent to use, or carrying concealed any slung-shot, billy, sand-club, metal knuckles, dagger, dirk, dangerous knife. Violators guilty of a felony.
Keywords: POSSESSION - NON-GUN ARMS